Clinicopathology study of necrotizing fasciitis with special reference to Fournier’s gangrene - Brar, Navjot; Dhaliwal, Jatinder Singh; Singh, Amanjot; Bajwa, Rajbir (International Surgery Journal, 2017)
Background: Necrotizing fasciitis including Fournier’s gangrene is an uncommon, critically serious infection of the subcutaneous tissue and fascia with relative sparing of the skin and muscle. Despite modern supportive measures, the reported mortality rate still is high and this is due to part to the aggressive nature of the infection. The present study was performed upon 50 patients to study clinicopathology of necrotizing fasciitis with special reference to Fournier’s gangrene. Methods: This cross-sectional study was conducted in Surgery ward of SGRD Hospital, for a period of 1 year (1st January 2015 to 31st December 2015). The performa filled for patients with necrotizing fasciitis was designed on the basis of NICE guidelines and details like history, examination, general survey, local examination, systemic examination and investigations, statistical analysis of data done. Results: Necrotizing fasciitis, though it is found at any age but is a disease of middle and old aged adults in this part of the world, being commonest in the 4th, 5th, 6th decades of life and is more common in males. The disease is more common in people with low socio-economic groups with poor personal hygiene, diabetes mellitus and history of drug addiction. Trauma is the most common predisposing factor for the necrotizing fasciitis as a whole whereas idiopathic cause is the most common cause in cases of Fournier’s gangrene. Polymicrobial infection is the most common variety, where in E. coli, Streptococcus, Bacteroids are most commonly isolated. Regarding monobacterial infection streptococcus being the most common. Conclusion: Current study showed increased frequency of necrotizing fasciitis in people aged above 40 years. Diabetes mellitus and other premorbid conditions increase the risk of mortality. Polymicrobial infection in combination of Escherichia coli, Streptococcus, Pseudomonas, Bacteroids and Staphylococcus were the most commonly found. Early debridement, parenteral combined antibiotic and supportive measure formed the basis of treatment. Septicemia was a common complication which was often cause death.